2000
DOI: 10.1614/0043-1745(2000)048[0541:eamomi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and metabolism of MON 37500 inTriticum aestivumand weedy grass species as affected by temperature and soil moisture

Abstract: Spray application of 24 and 46 g ha−1 MON 37500 was used in efficacy studies, and vacuum infiltration or droplet application of radiolabeled MON 37500 was used in metabolism studies to evaluate temperature and soil moisture on MON 37500 efficacy and metabolism. Day/night temperatures before vs. after application of MON 37500 of 25/23 vs. 25/23, 25/23 vs. 5/3, 5/3 vs. 25/23, and 5/3 vs. 5/3 C were evaluated for the efficacy study, whereas day/night temperatures of 5/3 and 25/23 C were used for the metabolism st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 29 publications
3
57
0
2
Order By: Relevance
“…Also, the results of this work support the hypothesis that oat crop tolerance to iodosulfuron-methyl is temperature- (Koeppe et al, 2000). Also, the sulfonylurea sulfosulfuron injury to wheat plants was higher at 21/7 o C (day/night) than at 10/5 o C (Geier et al, 1999), in part, because at lower temperatures plants have reduced leaf area, thus reduced absorption and translocation of the herbicide (Olson et al, 2000).…”
Section: Resultssupporting
confidence: 77%
“…Also, the results of this work support the hypothesis that oat crop tolerance to iodosulfuron-methyl is temperature- (Koeppe et al, 2000). Also, the sulfonylurea sulfosulfuron injury to wheat plants was higher at 21/7 o C (day/night) than at 10/5 o C (Geier et al, 1999), in part, because at lower temperatures plants have reduced leaf area, thus reduced absorption and translocation of the herbicide (Olson et al, 2000).…”
Section: Resultssupporting
confidence: 77%
“…Negative effects were seen on wheat subjected to chlortoluron (Banting et al 1976), while no injury was observed when sulfosulfuron was applied on wheat exposed to different temperature cycles (25/238C vs. 5/38C) (Olson et al 2000). Other studies in cold chambers have been done on spring wheat (Xie et al 1994) or barley (McMullan 1994) exposed to one or two herbicides and the results were mixed, depending on the species and herbicide used.…”
mentioning
confidence: 99%
“…Under adverse soil-weather conditions, such as low * Means within weed species followed by the same letter are not significantly different at p = 0.05. temperature, relative humidity and soil moisture, herbicide activity may be reduced considerably giving lower efficacy than expected, while under optimal circumstances i.e. high relative humidity and sufficient soil moisture, herbicides achieve better weed control efficacy (Olson et al 2000, Kumaratilake & Preston 2005. In the present study, air temperature, relative humidity and soil moisture considerably affected tribenuron methyl activity on A. arvensis and S. media.…”
Section: Discussionmentioning
confidence: 52%
“…Tribenuron methyl is recommended to be used in combination with an adjuvant. Previous papers have reported that environmental conditions affect the activity of tribenuron methyl and other sulfonylurea herbicides (Kudsk et al 1990, Olson et al 2000. It has also been reported that the impact of climatic factors depends on weed species and can be modified in tank mix with adjuvants (Mathiassen & Kudsk 2002, Bunting et al 2004, Stagnari et al 2006, Aliverdi et al 2009, Pannacci et al 2010.…”
Section: Introductionmentioning
confidence: 99%